Análise de laudos emitidos sobre "prédios tipo caixão" da região metropolitana de Recife : causas apontadas para os desabamentos e interdições - Mélo, Mauro José Araújo Campelo de (2007)
In the past 20 years, some cities of the Metropolitan Area of Recife - PE, have been affected by several problems in Civil Engineering constructions, some of which resulted in human deaths. The most serious of these problems, given the number of constructions involved, concerns the specific building called box ; some of the buildings did fall and several others have been interdicted. Just a few of them were cleared and the majority of them continue to be interdicted. The general objective of the present dissertation is to analyze the awards produced on the building type box , built in the cities of Olinda, Jaboatão dos Guararapes and Paulista. Its goal is to study the causes pointed out as responsible for the collapse and interdictions of those constructions. In a general way, it can be pointed out as causes of the collapses, the following ones: imperfections or insufficiency of project (31.4%); low quality or inadequacies of the materials (17.1%); construction mistakes (34.4%); environmental causes (17.1%). For the interdictions: imperfections or insufficiencies of project (21.4%); low quality or inadequacies of the materials (3.5%); construction mistakes (2.8%); inadequate use or lack of maintenance (26.0%); environmental causes (4.3%); other causes (42.0%). The buildings were cleared when the conditions made by the Civil Defense of each city were met; they involved structural problems and habitability. It s also evident an inadequate performance of the inspection agencies and the lack of standardization of the awards, as well as the absence of a model for the adequate recovery of these constructions. One expects to have contributed, through the analysis and systematization of the data contained in the studied awards, for future works, aiming at the development of technology capable to equate the situation of the cited real estates.